2012
DOI: 10.1590/s0482-50042012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Análise neuropsicológica de distúrbios cognitivos em pacientes com fibromialgia, artrite reumatoide e lúpus eritematoso sistêmico

Abstract: Introduction: This study assesses the possible existence of cognitive disorder associated with chronic diseases [fi bromyalgia (FM), rheumatoid arthritis (RA) and lupus (SLE)], and the infl uence of the variables age, educational level and psychiatric symptoms on those disorders. Materials and methods: The patients were referred by the Rheumatology Outpatient Clinic of the Hospital Universitário de Brasília (HUB), with ages ranging from 30 to 80 years, and were divided into the following three groups: FM, 13 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 21 publications
2
12
0
2
Order By: Relevance
“…In agreement with previous studies, we reported a worse cognitive function in RA patients than that in healthy controls [1,2,3,4]. It has recently been shown that patients with RA had reduced performance in tests assessing the cognitive spheres of visual-constructional apraxia [1].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies, we reported a worse cognitive function in RA patients than that in healthy controls [1,2,3,4]. It has recently been shown that patients with RA had reduced performance in tests assessing the cognitive spheres of visual-constructional apraxia [1].…”
Section: Discussionsupporting
confidence: 92%
“…It has recently been shown that patients with RA had reduced performance in tests assessing the cognitive spheres of visual-constructional apraxia [1]. In addition, individuals with RA had cognitive impairments in domains associated with executive function, visual-spatial learning/memory and verbal learning/memory [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was verified the predominance of women in this sample and similar results to other studies. [2,3,[26][27][28] According to Mota et al, [9] RA preferentially affects women in a ratio of 3:1. In the same way, authors affirm that SLE also affects women, but young ones and in a ratio of 10:1.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatic diseases are chronic diseases that generate negative implications in the physical, psychological and social spheres in their patients. [1] Systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are examples of rheumatic diseases (RD), [2,3] characterized by persistent inflammatory reactions, especially articular ones, accompanied by pain and fatigue and alteration of the body image. [3] Rheumatoid arthritis is a systemic and progressive inflammatory disease that affects individuals of productive age leading to the loss of labor capacity, an important limitation in functional capacity and quality of life, [4][5][6] due to its clinical manifestations, which may be both articular and extra-articular.…”
Section: Introductionmentioning
confidence: 99%